2021
DOI: 10.1007/s10841-021-00352-5
|View full text |Cite
|
Sign up to set email alerts
|

Canopy arthropod diversity associated with Quercus laurina: importance of an oak species diversity gradient on abundance, species richness and guild composition

Abstract: Central-west and south of Mexico are particularly rich in oak species, coexisting from two to six species and generating gradients of oak diversity that could potentially affect community structure of canopy arthropods. We evaluated changes in canopy arthropod diversity of the Quercus laurina along a gradient of oak diversity in the central-west portion of the Trans-Mexican Volcanic Belt. Five study sites that represent an oak diversity gradient and, where Q. laurina is also widespread were selected. At each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The parasitoid species composition was highly congruent with that of the galling insects. Our results agree with previous studies indicating that parasitoid species composition is modulated by host species composition (Hrcek et al, 2013; Peralta et al, 2018; Vaca‐Sánchez et al, 2021). Different morphological characteristics of the galls, such as wall thickness, size and occurrence of trichomes, are obstacles for parasitoids, which cannot find and oviposit in their host (Hawkins & Gagné, 1989; Hernández‐López et al, 2021; László & Tóthmérész, 2013; Luz et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The parasitoid species composition was highly congruent with that of the galling insects. Our results agree with previous studies indicating that parasitoid species composition is modulated by host species composition (Hrcek et al, 2013; Peralta et al, 2018; Vaca‐Sánchez et al, 2021). Different morphological characteristics of the galls, such as wall thickness, size and occurrence of trichomes, are obstacles for parasitoids, which cannot find and oviposit in their host (Hawkins & Gagné, 1989; Hernández‐López et al, 2021; László & Tóthmérész, 2013; Luz et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Vaca‐Sánchez et al . (2021) found that canopy arthropods are more abundant and diverse in diverse Quercus forests, which provide diverse ecological niches for the arthropods, than in less diverse Quercus forests. Their results suggest that the availability of resources is a significant factor in shaping the assemblages of surface‐active arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of plant phylogenetic diversity has been extensively documented in various ecological contexts, including nurse‐plant interactions (Navarro‐Cano et al., 2017, 2019; Valiente‐Banuet & Verdú, 2007), soil erosion control (Bochet et al., 2000), the spread of pests and pathogens (Gilbert & Webb, 2007) and tri‐trophic interactions (Alavez et al., 2023). However, there is limited experimental evidence on the relationship between plant phylogenetic distance and arthropod communities, particularly in highly diverse ecosystems such as tropical forests (Moreira et al., 2016; Scherber et al., 2010; Vaca‐Sánchez et al., 2021).…”
Section: Introductionmentioning
confidence: 99%